Variasi Konsentrasi Neutral Buffer Formalin Pada Proses Fiksasi Jaringan Histologi Ginjal Mencit - Kayni, Ika Mareta Nur; Nailufar, Yuyun; Rahmawati, Yeni (Anakes : Jurnal Ilmiah Analis Kesehatan, 2025)
Neutral Buffer Formalin 10% is commonly used to fix tissue whose structure will be observed. The observation is carried out to diagnose the disease. Poor fixation results will affect further tissue processing. The right concentration and fixation time will also produce quality tissue preparations and the right diagnosis. This study determined the quality of the hematoxylin-eosin staining results in the mouse kidney fixation process with variations in NBF concentrations of 5%, 10%, 15%, and 20%. This research method is observational by fixing the mouse kidney organ in NBF with concentrations of 5%, 10%, 15%, and 20% for 24 hours at room temperature. The results of the study are in the form of scores, which are then processed using the Kruskal-Wallis Test. Based on the total scoring results, NBF 10% is the best concentration. The result of the Kruskal-Wallis test is p ≤ 0.05, which means there is a significant difference, and the Posthoc test result is that the NBF concentration of 15% is a concentration that has no significant difference with the control. While NBF 5% and 20% have significant differences from the NBF 10% control. Thus, NBF 10% is the best concentration, and NBF 15% has better assessment results than NBF 5% and 20%. Keywords: Fixation, Neutral Buffer Formalin, Hematoxylin Eosin